2011
DOI: 10.1016/j.jvs.2010.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Tetramethylpyrazine protects spinal cord and reduces inflammation in a rat model of spinal cord ischemia-reperfusion injury

Abstract: Treatment with TMP exerted a neuroprotective effect against spinal cord ischemia-reperfusion injury. The anti-inflammatory effect was believed to be one of the contributing mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 35 publications
0
56
0
1
Order By: Relevance
“…5,6 SUMOylation is involved in many of the processes activated in the post-ischemic spinal cord. These include DNA damage repair, 16,17 ubiquitin conjugation and proteasomal degradation of proteins, 18,19 NF-kB activation, 20,21 hypoxia-inducible factor activation 22,23 and oxidative stress. 24,25 Therefore, the post-ischemic activation of SUMO2/3 conjugation is highly likely to have a major impact on the fate of post-ischemic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 SUMOylation is involved in many of the processes activated in the post-ischemic spinal cord. These include DNA damage repair, 16,17 ubiquitin conjugation and proteasomal degradation of proteins, 18,19 NF-kB activation, 20,21 hypoxia-inducible factor activation 22,23 and oxidative stress. 24,25 Therefore, the post-ischemic activation of SUMO2/3 conjugation is highly likely to have a major impact on the fate of post-ischemic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…TMP has been identified with several molecular targeting properties, and demonstrates a broad therapeutic capacity such as scavenging oxygen free radicals (Li et al, 2009;Fan et al, 2011). It has antiapoptotic effect associated with down-regulating the expressions of Bcl-2 and Bcl-2 Associated X protein (bax) along with suppressing of caspase-3 (Chang et al, 2007).…”
Section: Research Articlementioning
confidence: 99%
“…On day 7 post hatch, after induction of TD, thiram group was equally divided into two groups designated as TD group (n=60) and TMP treatment group (n=60). TMP group was treated with Tetramethylpyrazine @ 30 mg/kg/day (Fan et al, 2011;Shin et al, 2013;Zhang et al, 2015) by intraperitoneal route from day 7 to day 18.…”
Section: Experiments Designmentioning
confidence: 99%
“…Previous investigations have also demonstrated that increased oxidative stress, neuroinflammation, and apoptotic cell death are associated with SCII [6, 7]. In particular, numerous studies have established that SCII is intimately linked to inflammatory responses and the upregulation of proinflammatory cytokines and chemokines [8, 9]; therefore, natural products containing bioactive molecules with anti-inflammatory properties possess potential as an alternative approach to improve SCII-induced neurological deficits and tissue injuries [10-12]. …”
Section: Introductionmentioning
confidence: 99%